Molecular Diagnosis of Lung Cancer - Savelina Popovska; Tereza Dineva; Polina Damyanova (Journal of Biomedical & Clinical Research)
Lung cancer is still the leading cancer-related cause of death with a high incidence rate in the whole world. Treatment options – surgery, radiotherapy, and chemotherapy, depending on the stage of the disease. During the last decade, many molecular alterations were discovered that led to impressive changes in treatment. Personalized approaches, including target therapies with specific inhibitor drugs, became a part of the standard therapies. This article reviews current molecular biomarkers used in clinical practice to treat lung cancer patients.